Foaming of AA 6061 using multiple pieces of foamable precursor - Duarte, Isabel (2019)
Aluminium foams were produced by expanding multiple pieces of foamable precursor inside a mould instead of using a single piece. The kinetics of foam formation and mould filling were visualised in situ by X-ray radioscopy. It was found that foaming of multiple precursor materials leads to the best result when the growth directions of the individual precursor pieces are perpendicular to each other. X-ray tomography was used to study the internal structure of the foams in 3D. High local densities in joining regions and in areas of delayed pore nucleation were observed.